"Dynamic Multi-Objective Task Scheduling Framework for Mobile Cloud Computing" - Rameshwar Singh Sikarwar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Mobile Cloud Computing (MCC) has emerged as a promising paradigm to extend the computational capabilities of resource-constrained mobile devices by offloading intensive computation tasks to remote cloud servers. Efficient task scheduling plays a crucial role in improving the performance of MCC systems by maximizing resource utilization, minimizing energy consumption, and reducing latency. In this paper, we propose a unique multi-objective task scheduling approach specifically designed for MCC environments. The proposed scheme aims to balance multiple conflicting objectives, including resource utilization, energy consumption, and task completion time. We formulate the task scheduling problem as a multi-objective optimization problem and present a heuristic-based solution to efficiently allocate tasks to appropriate cloud and mobile resources. Experimental evaluations demonstrate the superiority of the proposed method over existing approaches, achieving better trade-offs among competing objectives.